Big data and decision-making : applications and uses in the public and private sector - Visvizi, Anna, 1976-; Troisi, Orlando; Grimaldi, Mara (Emerald studies in politics and technology., 2023)
Big data and its accompanying technological ecosystems have had a dramatic impact on business, politics and society. At the same time, the very nature of big data, a term that originates from computer science discourse, often remains opaque to research communities in other disciplines as well as to practitioners. Considering the pervasive impact of big data across a number of issues and domains, clearer insight into its functions and practical application is needed. Through a unique blend of case studies and critical analysis, Big Data and Decision-Making: Applications and Uses in the Public and Private Sector examines how big data influences contemporary societies in decision-making processes, strategy setting and overall performance. Covering topics ranging from data privacy to AI, big data in healthcare, SMEs, tourism and smart cities, contributors offer a critical appraisal of lessons learnt in the process of harnessing the promise inherent in big data. Big Data and Decision-Making: Applications and Uses in the Public and Private Sector breaks down the concept of big data to reveal how it has become integrated into the fabric of both public and private domains, as well as how its value can ultimately be exploited. To this end, its contributors call for the building of bridges between the computer science-driven debate on big data and research taking place in social sciences and management.